RETRACTED: A CLINICAL CASE: VIRUS ENCEPHALITIS - O. A. Shavlovskaya (Сеченовский вестник, 2013)
RETRACTED ARTICLEThe review researches on a case of a virus encephalitis associated with a cytomegalovirus and herpes simplex virus. Diagnostics of encephalitis is based on definition of specific antibodies to a virus of herpes and a cytomegalovirus in blood. Anamnesis data: the patient of 46 years, at the age of 20 years the patient transferred attack of varicella-zoster virus with localization in a face, till 39 years of herpetic virus attacks wasn’t, during the period from 43 to 45 years neurologic manifestations in the form of a lung left-side hemiparesis gradually began to accrue. To 46 years have a herpetic throat infection. MRI: diff use hyperintense lesion of white substance; the evoke potentials of different modalities and eye — normal. Immunological status: the antibodies of a class G to a cytomegalovirus was 39,66 E/ml is raised, at repeated research in 1 month is noted increase of a caption of antibodies of a class G to a cytomegalovirus to 200,4 AE/ml, and the caption of antibodies to a virus of simple herpes of I type to 7,51 E/ml is raised. Against continuous therapy by anti-virus preparations (valtrex, famvir) it is received positive dynamics of clinical manifestations, is absent negative dynamics on MRI.